Characterization of processes responsible for the distinct effect of herbicides DCMU and BNT on Photosystem II photoinactivation in cells of the cyanobacterium Synechococcus sp. PCC 7942 - Komenda, J; Koblízek, M; Prásil, O (Photosynthesis research, 2000)
Light-induced modification of Photosystem II (PS II) complex was characterized in the cyanobacterium Synechococcus sp. PCC 7942 treated with either DCMU (a phenylurea PS II inhibitor) or BNT (a phenolic PS II inhibitor). The irradiance response of photoinactivation of PS II oxygen evolution indicated a BNT-specific photoinhibition that saturated at relatively low intensity of light. This BNT-specific process was slowed down under anaerobiosis, was accompanied by the oxygen-dependent formation of a 39 kDa D1 protein adduct, and was not related to stable Q(A) reduction or the ADRY effect. In the BNT-treated cells, the light-induced, oxygen-independent initial drop of PS II electron flow was not affected by formate, an anion modifying properties of the PS II non-heme iron. For DCMU-treated cells, anaerobiosis did not significantly affect PS II photoinactivation, the D1 adduct was not observed and addition of formate induced similar initial decrease of PS II electron flow as in the BNT-treated cells. Our results indicate that reactive oxygen species (most likely singlet oxygen) and modification of the PS II acceptor side are responsible for the fast BNT-induced photoinactivation of PS II.